THE CONCEPT OF IRONY IN JANE AUSTEN’S NOVELS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Jane Austen’s fiction is distinguished by its nuanced and deliberate use of irony, which operates as a central mechanism for social criticism, character exploration, and thematic complexity. This paper examines the diverse manifestations of irony—including verbal, situational, and dramatic forms—in three of Austen’s key novels: Pride and Prejudice (1813), Emma (1815), and Persuasion (1817). Through detailed textual analysis, the study illustrates how irony reveals the tensions between outward appearances and underlying realities within Regency society, especially regarding marriage, class hierarchy, and gender roles. Austen’s ironic narrative stance, frequently articulated through free indirect discourse, establishes a reflective distance that encourages readers to reassess social conventions while maintaining a tone of restrained humor. The analysis indicates that irony in Austen’s novels extends beyond comic effect, functioning as an ethical framework that promotes self-recognition and moral development in both characters and readers. This sustained use of irony plays a vital role in the lasting relevance and intellectual richness of Austen’s literary works.